Improving the Efficiency of Banks’ Green Financing in Uzbekistan and Kazakhstan - Maxmudov Rahimjon Hamid o‘g‘li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
Climate change and the global shift toward low-carbon development are forcing banking sectors to rethink how capital is allocated. For emerging economies like Uzbekistan and Kazakhstan, efficient green financing is becoming a strategic requirement: both countries aim for carbon neutrality by 2060, both face outdated energy infrastructure, and both need private capital to modernize their economies. Commercial banks sit at the center of this transition. However, their green lending remains limited due to weak project pipelines, insufficient ESG integration, low awareness, and limited regulatory incentives.